Faktor-faktor yang Memengaruhi Fungsi Anus setelah Prosedur PSARP pada Pasien Malformasi Anorektal - Suryoprabowo, Vincent; Lampus, Harsali F.; Rendy, Leo (e-CliniC, 2026)
Abstract: In anorectal malformations (ARM), posterior sagittal anorectoplasty (PSARP) procedure is the standard management, however, the anorectal functional outcomes vary. This study aimed to assess the factors affecting anorectal function after the PSARP procedure using the Rintala score. This was a retrospective cohort study of 29 ARM patients who underwent PSARP at Prof. Dr. R. D. Kandou Hospital Manado during the 2019–2022 period. Medical records and patient follow-up data were analyzed using the chi-square test and linear regression. The results showed that of the 29 patients (13 males, 16 females), 86.2% underwent staged repair, while the rest had one-stage repair. The mean Rintala score was 14.59±4.17; 24.1% had normal function, 62.1% good, 6.9% fair, and 6.9% poor. Adequate bowel management was performed in all patients. Surgical wound infection was found in one patient (3.4%). Re-do PSARP was performed in four patients (13.8%). There were no cases of malnutrition or musculoskeletal abnormalities. Syndromic diseases were found in three patients (10.3%). Multivariate analysis showed that no variables were significantly associated with the Rintala score (p>0.05). In conclusion, the majority of patients have good–normal anal function after PSARP. There is no significant relationship between bowel management, surgical wound infection, redo PSARP, malnutrition, musculoskeletal abnormalities, or syndromic diseases and anal function. Continuous bowel management education remains important for long-term outcomes. Keywords: anorectal malformation; PSARP; anal function; Rintala score    Abstrak: Pada malformasi anorektal (MAR), prosedur posterior sagittal anorectoplasty (PSARP) merupakan standar tatalaksana, namun luaran fungsi anus bervariasi. Penelitian ini bertujuan untuk menilai faktor-faktor yang memengaruhi fungsi anus setelah prosedur PSARP menggunakan skor Rintala. Jenis penelitian ialah kohort retrospektif terhadap 29 pasien MAR yang menjalani PSARP di RSUP Prof. Dr. R. D. Kandou Manado periode 2019–2022. Data rekam medis dan follow-up pasien dianalisis menggunakan uji chi-square dan regresi linear. Hasil penelitian mendapatkan dari 29 pasien (13 laki-laki, 16 perempuan), 86,2% menjalani staged repair, sisanya one stage repair. Skor Rintala rerata 14,59±4,17; 24,1% fungsi normal, 62,1% baik, 6,9% cukup, dan 6,9% buruk. Businasi adekuat dilakukan pada seluruh pasien. Infeksi luka operasi ditemukan pada satu pasien (3,4%). Re-do PSARP dilakukan pada empat pasien (13,8%). Tidak terdapat kasus malnutrisi maupun kelainan muskuloskeletal. Penyakit sindromik penyerta ditemukan pada tiga pasien (10,3%). Analisis multivariat menunjukkan tidak terdapat variabel yang berhubungan bermakna dengan skor Rintala (p>0,05). Simpulan penelitian ini ialah mayoritas pasien memiliki fungsi anus baik–normal pasca-PSARP. Tidak terdapat hubungan bermakna faktor businasi, infeksi luka operasi, re-do PSARP, malnutrisi, kelainan muskuloskeletal, maupun penyakit sindromik terhadap fungsi anus. Edukasi businasi berkelanjutan tetap penting untuk luaran jangka panjang. Kata kunci: malformasi anorektal; PSARP; fungsi anus; skor Rintala